Transthyretin Amyloidosis in Aged Vervet Monkeys, as a Candidate for the Spontaneous Animal Model of Senile Systemic Amyloidosis - Nakamura, Shinichiro; Ueda, Mitsuharu; Ageyama, Naohide; Ando, Yukio; Torii, Ryuzo (IntechOpen, 2011)
None